HUBUNGAN PENGETAHUAN IBU TENTANG KEJANG DEMAM DENGAN SIKAP IBU TERHADAP PENANGANAN KEJANG DEMAM PADA BALITA - yektiningsih, Erwin; Sukarsih, Anik (Jurnal AKP, 2013)
Convulsion fever is a convulsion that occur on the rise (temperature above 380 C). Convulsion fever experienced by many children that usually occurs in early child fever would seemÂ  strange for a while , then stiff, convulsive and rolled her eyes. Families, especially mother whose knowledge is less generally indicatesÂ  the attitude of panicÂ  or consider their children possessed. The purpose of this research was to know the relationsof motherâs knowledge about convulsion fever with motherâs attitude to intervention convulsion fever in child age under five years.The research design used cross sectional. With samples amount to 44 respondents who fulfilled the criteria of incuslion and exclusion. Intake of sample used technique of simple random sampling.Base on the research results obtained that most of mothers have good knowledge that is amount to 19 respondentsÂ  (43,2%) and motherâs attitude to intervention convulsion fever at child that positive amount to 24 respondents (54,5%). Based on the test result of Correlaton Coefficiente Contingency obtained significant value ofÂ  0.000 < 0,05 , which means ho wes rejected. This means that there was relation of motherâsÂ  knowledge about convulsion fever with motherâs attitude to intervention convulsion fever in child age under five years with strong category.Motherâs knowledge about convulsion fever, increase the knowledge, information, supervise and pay attention to its chid age under five years if happened continuous fever, those were things that must be paid attention by the mothers, so mothers did not panic and know how to behave in case of colfusions fever in child age under five years.Â Keywords: Knowledge, mother, attitude, convulsion fever, child age under five years